2009
DOI: 10.1007/s11906-009-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct renin inhibition: An update

Abstract: Aliskiren, the first orally effective direct renin inhibitor, is an effective antihypertensive agent with distinctive properties including placebo-like tolerability, pharmacologic effects that persist after drug discontinuation, and a unique mechanism of action. When combined with agents that inhibit the renin-angiotensin-aldosterone system (RAAS), such as angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, or beta-blockers, additional blood pressure reduction reflects more complete RAAS b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The mechanisms of aliskiren action include enzymatic blockade of renin and prorenin at the site of the (pro)renin receptor, finally leading to a decrease in blood pressure. In patients with diabetic nephropathy, adding aliskiren to losartan resulted in an additional 20% reduction in urinary protein excretion as well [26]. A total of 13 randomized controlled trials with 12,222 patients indicated that aliskiren in combination therapy with angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers had remarkable effects in reducing both systolic and diastolic blood pressure when compared with angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers monotherapy, but with significantly increased risk of hyperkalaemia and kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of aliskiren action include enzymatic blockade of renin and prorenin at the site of the (pro)renin receptor, finally leading to a decrease in blood pressure. In patients with diabetic nephropathy, adding aliskiren to losartan resulted in an additional 20% reduction in urinary protein excretion as well [26]. A total of 13 randomized controlled trials with 12,222 patients indicated that aliskiren in combination therapy with angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers had remarkable effects in reducing both systolic and diastolic blood pressure when compared with angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers monotherapy, but with significantly increased risk of hyperkalaemia and kidney injury.…”
Section: Discussionmentioning
confidence: 99%